El amor a las letras: una escuela y su maestro en Uberlândia/ MG (1919/1933) - Sandra Cristina Fagundes de Lima (Universidade Federal de Rondônia, 2018)
In this paper we have searched the trajectory of a private school founded   by teacher Jerônimo Arantesin Uberlândia city, during the first Republic (1919-1933), the Amor às Letras School. To accomplish this search, we consulted printed documents (meeting records, class diary, newspapers, magazines, final tests, photographs etc), as well as oral sources. Although placed at Uberlândia, we must   not forget that Amor àsLetrasSchool was inserted in a national context of debates between defenders of a school renewed in methods and subjects and those devoted to maintain a school organized under traditional proposes. In this meaning, the analysis of the school trajectory of teacher Arantes, at that time suggested the following problematic: due to the shock between the principles of the traditional school, criticized by reformists, and the flaunted presupposed of a  pedagogy  renewed in methods and subjects, how did Arantes acted in hisschool?